STRUCTURIZATION OF OWN FUEL-ENERGY RECOURSES OF THE REPUBLIC OF BELARUS IN BASIC DIRECTIONS OF CONSUMPTION - Y. N. Rumiantsava (Наука и техника)
On the basis of an analysis of scientific, reference and encyclopaedic literature, statistical information, and also main documents concerning power engineering policy a composition systemization of «own fuel-energy recourses» and «local fuel-energy recourses» categories in the Republic of Belarus is given in the paper. The paper also contains a structurization of power resources of the mentioned categories in accordance with directions of consumption of fuel-energy resources for generation of heat and electrical energy and usage of fuel-energy resources directly as a fuel.In order to increase an objectivity of actual and forecasting estimations of efficiency in respect of power resources’ usage  the paper proposes to analyze consumption of every fuel-energy resources’ type/group separately in accordance with basic directions of consumption but not as a part of boiler-oven fuel. Local fuel-energy recourses are to be considered not as end in itself, but only as a part of own fuel-energy recourses of the Republic of Belarus.